2016
DOI: 10.1242/dev.145862
|View full text |Cite
|
Sign up to set email alerts
|

DUX4 induces a transcriptome more characteristic of a less-differentiated cell state and inhibits myogenesis

Abstract: Skeletal muscle wasting in facioscapulohumeral muscular dystrophy (FSHD) results in substantial morbidity. On a disease-permissive chromosome 4qA haplotype, genomic and/or epigenetic changes at the D4Z4 macrosatellite repeat allows transcription of the DUX4 retrogene. Analysing transgenic mice carrying a human D4Z4 genomic locus from an FSHD-affected individual showed that DUX4 was transiently induced in myoblasts during skeletal muscle regeneration. Centromeric to the D4Z4 repeats is an inverted D4Z4 unit enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 48 publications
(97 reference statements)
2
6
0
Order By: Relevance
“…Lastly, in agreement with GTEx data (Table S3), we demonstrated that the DUX4c protein was expressed in testis, as previously shown for the homologous DUX4 protein [35]. Knopp et al [14] proposed that both DUX4 and DUX4c target genes were involved in urogenital development. However, in contrast to DUX4, which was detected in spermatogonia and spermatocytes I [35], we found DUX4c staining generally located Fig.…”
Section: The Dux4c Protein Is Expressed In Human Differentiating Musc...supporting
confidence: 92%
See 4 more Smart Citations
“…Lastly, in agreement with GTEx data (Table S3), we demonstrated that the DUX4c protein was expressed in testis, as previously shown for the homologous DUX4 protein [35]. Knopp et al [14] proposed that both DUX4 and DUX4c target genes were involved in urogenital development. However, in contrast to DUX4, which was detected in spermatogonia and spermatocytes I [35], we found DUX4c staining generally located Fig.…”
Section: The Dux4c Protein Is Expressed In Human Differentiating Musc...supporting
confidence: 92%
“…S3A) and appeared like comets with a DUX4c cytoplasmic staining at one side (as reported in immortalized cells, [12]). We also observed DUX4c in larger myotubes, specifically in TnT intense areas found either next to clusters of nuclei (circle), at a tip of the cell, next to the membrane, at cell-cell contacts or next to a very thin extension (characteristic of DUX4-expressing muscle cells, [14]). At day 6, we unexpectedly observed in only two myotubes close to each other (of all the analyzed fields) a DUX4c nuclear labeling with the rat antiserum (Fig.…”
Section: Dux4c Protein Detection In Primary Fshd Muscle Cellsmentioning
confidence: 58%
See 3 more Smart Citations